Association analysis between rs1899663 HOTAIR gene polymorphism and bladder cancer development in Ukrainian population - A. D. Volkohon; Ya. D. Chumachenko; V. Yu. Harbuzova; O. V. Ataman (Zaporožskij Medicinskij Žurnal)
HOX antisense intergenic RNA (HOTAIR), the well-known long noncoding RNA (lnRNA), performs epigenetic regulation of cell cycle genes expression. Based on this fact it can be assumed that HOTAIR single nucleotide polymorphisms (SNPs) affect the development of different oncological processes, in particular, bladder cancer.